PENINGKATAN KEMAMPUAN KOGNITIF BELAJAR MATEMATIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DI KELAS VII – 8 SMP NEGERI 4 MEDAN - WARNI . (Universitas Negeri Medan, 2014)
The mathematic learning in SMP Negeri 4 Medan not yet give the classical studying completeness without remedical programme. The condition is caused by model, method, and teaching – learning strategy is not yet can increase the student’s studying cognitive capability and not actived of student in teaching – learning process. The class acting research will be passed in two cycles. From cycle to cycle use the cooperative learning models tipe Student Team Achievement Division (STAD) by always increase the learning application quality is orientated the student activity which disembogue on student’s studying cognitive capability (result). The research is involved on student in class of VII – 8 SMP Negeri 4 Medan by amount of 30 students. After the research occur during two cycles can be concluded that; 1) Student/s studying cognitive capability (result) by applicated the cooperative learning models tipe Student Team Achievement Division (STAD) on cycle I the average is 62,7 by classical result is 53,33% and on the second cycle II the average is 87,3 by classical result is 86,66% that indicated complete individually and class accord CCM of mathematics which applicated in SMP Negeri 4Medan; 2) Student activity data accord the observer observation on cycle I between others reading / writing (45,71%), doing (16,36%), asking for friends (6,36%) asking to the teacher (7,27%) and not relevant with teaching – learning process (4,55%). Student activity data accord the observation on cycle II between other reading / writing (28,75%), doing (43,13%), asking for friends(20,00%) asking for the teacher (4,38%) and not relevant with teaching – learning process (3,75%). From the above data occur the student studying activity increasing accord the hope by applicated the cooperative learning models tipe Student Team Achievement Division (STAD). Kata kunci: Cooperative Learning Models type Student Team Achievement Division (STAD), Triangle and Rectangular, Student Activity